A model evaluation exercise for non-buoyant releases from continuous point sources. (1st January 2000) - Ulke, A.G.
A model of the dispersion of pollutants released from a continuous point source into the atmospheric boundary layer is suggested. For this model and for that of Gryning et al. (1987), the predicted normalised crosswind integrated concentrations are compared with observational data. The data obtained in diffusion experiments with a non-depositing tracer, in non-buoyant releases carried out at Copenhagen (Denmark), Cabauw (The Netherlands), Hanford (USA) and Lillestrom (Norway) have been used. The former two experiments were elevated releases during near neutral and unstable conditions; the latter two were near surface releases during near neutral and stable conditions. The comparison is done with each dataset and with the full database. Statistical measures and techniques of model evaluation are obtained and applied. The behaviour of residuals with some meteorological parameters is studied. The overall agreement between estimated and measured concentrations is satisfactory. The models have quite similar performances.